Probability Distribution of Multiple-Access Interference in Chaotic Spreading Codes based on DS-CDMA Communication System - Litvinenko, A.; Bekeris, E. (Elektronika ir Elektrotechnika, 2012)
This paper is devoted to the evaluation of the probability distribution of the multiple access interference in asynchronous Direct Sequence Code Division Multiple Access (DS CDMA) communication system based on chaotic spreading sequences. Statistical properties of such interference in a system with K users causing the multiple-access interference are obtained by a computer simulation. Simulation is carried out for the spreading sequences produced by the logistic map; the length of sequences: N = 7, 31, 63 and the number of users correspondingly: K = (3, 8, 11); (11, 32, 65); (64, 129). Ill. 3, bibl. 8, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.123.7.2380